Differentiation of Molecular Genotypes and Virulence Phenotypes of Puccinia triticina from Common Wheat in North America - Ordonez, M.E; Kolmer, J.A (Phytopathology, 2009)
Wheat leaf rust caused by Puccinia triticina is widely distributed in the wheat growing regions of the United States and Canada, and is subject to selection for virulence phenotype by leaf rust resistance genes in wheat cultivars. The objective of this study was to determine the number of genetically differentiated groups of P. triticina that are currently present in North America. In total, 148 isolates of P. triticina from the 1980s to 2005 were collected from wheat-growing regions of the United States and Canada and tested for virulence on 20 lines of wheat with single genes for leaf rust resistance and for molecular genotype with 23 simple sequence repeat (SSR) markers. In total, 91 virulence phenotypes and 65 SSR genotypes were found. After removal of isolates with identical virulence and SSR genotypes, 125 isolates were included for further analysis. Bayesian cluster analysis indicated five different groups of isolates based on SSR genotypes that also differed for virulence to leaf rust resistance genes Lr2a, Lr2c, Lr3bg, Lr17, and Lr28. Isolates avirulent to Lr14a and Lr20 that have increased since 2003 had SSR genotypes identical or similar to older isolates in one of the five groups, indicating that these isolates were derived by mutation from the previously existing population of P. triticina. The representative collection of P. triticina isolates had characteristics consistent with an asexual dikaryotic population of genetically differentiated groups of SSR genotypes with high levels of heterozygosity and disequilibrium within which stepwise mutation at avirulence or virulence loci regularly occurs.